Dynamic Interaction Between Organellas In the Management of Cytosolic Calcium Huvecs Exposed to 22 mM Glucose With Different Period Exposure - Olly Indrayani PWM; Djanggan Sargowo; Mochammad Aris Widodo; Rully MA Roesli; S Sumarno (The Indonesian Heart Association, 2007)
Background.In our previous research, when cell culture were exposed to high glucose, this will cause the increase of H2O2. At the exposure to 22 mM glucose on 3rd day, the increase of H2O2 that induced the activation of Phospholipase C (PLC) have caused 1P3 (Inositol tri-phosphate) mobilizing the release of Ca²+ from the depo Endoplasmic reticulum (ER). Thus, causing the increase of cytosolic Ca²+. Giving thapsigargin (TG) will cause significant increase in Cytosolic Ca²+ so that the most contribution to the increasing of Cytosolic Ca²+ derives from the ER . On the 7th day exposure, H2O2 played the same role as TG, causing direct incease in Cytosolic Ca²+ and an addition of Ca²+ free/buffer ethyleneglyco bis (ßaminoethyl ether).&NNN’N’– tetraacetic acid (EGTA) caused significant decrease of cytosolic Ca²+ basal and the greatest contribution to the increase of cytosolic Ca²+ on the 7th day, comes from extracellular. Administrating Cyclosporin A (CSA) 10 µM on the 9th day, caused significant decreasing on cytosolic Ca²+ basal, the ability of CSA in decreasing Ca²+ basal concentration was less than the 3rd and 7th days. At a high glucose condition with different length of exposure, a change of new cytosolic Ca²+ homeostatic regulation occurred and this enable a change in the dynamic interaction among ER, extracellular and mitochondria.Method.HUVECs culture exposed to 22 mM glucose for 3, 7 and 9 days. The cells were incubated with FURA2-AM. The evaluation of fluorescence cytosolic Ca²+ was done by epifluorescence Nikon digital camera-computerized analyser. To measure the cytosolic Ca²+ concentration we use Histogram Image Corel Draw Photo Paint 12.Result. Exposure to glucose 22mM on the 3rd day (65.4 ± 12.2) it showed the increase of cytosolic Ca²+ by giving Ca²+ free/EGTA 1 mM and CSA 10 mM caused the decrease of cytosolic Ca²+ (33.2 ± 4.47) TG1µM and CSA caused the decrease of cytosolic Ca²+ basal (53.07 ± 2.75) and Ca²+ -free/EGTA, TG and CSA (68.59 ± 5.71). On the 7th day exposure (92.74 ± 7.66) the decrease of cyto -solic Ca²+ basal occurred at the giving of Ca²+ -free/EGTA, TG (50.52 ± 9.23). EGTA and CSA (45.59 ±6.2). TG and CSA (73.55 ± 7.30), Ca²+ -free/EGTA and TG much more decrease the concentrate of cytosolic Ca²+ basal (17.58 ±4.5). On the 9th day of exposure to glucose (72.32 ±7.46), the giving of Ca²+ -free/EGTA, TG and CSA(35.76 ± 5.25) have caused the decrease of cytosolic Ca²+ basal. Conclusion.HUVECs culture exposed to 22mM glucose will cause the increase in H2O2and cytosolic Ca²+ basal. ER, mitochondria and extracellular regulate the Cytosolic Ca²+ and a dynamic interaction occurred among them to obtain a new homeostatic.